Gut microbiota and autism spectrum disorders: a bidirectional Mendelian randomization study - Li, Zhi; Liu, Shuai; Liu, Fang; Dai, Nannan; Liang, Rujia; Lv, Shaoguang; Bao, Lisha (Frontiers in Cellular and Infection Microbiology, 2023)
In recent years, observational studies have provided evidence supporting a potential association between autism spectrum disorder (ASD) and gut microbiota. However, the causal effect of gut microbiota on ASD remains unknown.We identified the summary statistics of 206 gut microbiota from the MiBioGen study, and ASD data were obtained from the latest Psychiatric Genomics Consortium Genome-Wide Association Study (GWAS). We then performed Mendelian randomization (MR) to determine a causal relationship between the gut microbiota and ASD using the inverse variance weighted (IVW) method, simple mode, MR-Egger, weighted median, and weighted model. Furthermore, we used Cochran's Q test, MR-Egger intercept test, Mendelian Randomization Pleiotropy RESidual Sum and Outlier (MR-PRESSO), and leave-one-out analysis to identify heterogeneity and pleiotropy. Moreover, the Benjamin-Hochberg approach (FDR) was employed to assess the strength of the connection between exposure and outcome. We performed reverse MR analysis on the gut microbiota that were found to be causally associated with ASD in the forward MR analysis to examine the causal relationships. The enrichment analyses were used to analyze the biological function at last.Turicibacter had a possible positive association with ASD (IVW OR=1.14, 95% CI: 1.00-1.29, P=3.7×10 −2 ), four gut microbiota with a potential protective effect on ASD: genus Dorea (OR=0.81, 95% CI: 0.69-0.96, P=1.4×10 −2 ), genus Ruminiclostridium5 (OR=0.81, 95% CI: 0.69-0.96, P=1.5×10 −2 ), genus Ruminococcus1 (OR=0.83, 95% CI: 0.70-0.98, P=2.8×10 −2 ), and genus Sutterella (OR=0.82, 95% CI: 0.68-0.99, P=3.6×10 −2 ). After FDR multiple-testing correction we further observed that there were two gut microbiota still have significant relationship with ASD:family Prevotellaceae (IVW OR=1.24; 95% CI: 1.09-1.40, P=9.2×10 -4 ) was strongly positively correlated with ASD and genus RuminococcaceaeUCG005 (IVW OR=0.78, 95% CI: 0.67-0.89, P=6.9×10 −4 ) was strongly negatively correlated with ASD. The sensitivity analysis excluded the influence of heterogeneity and horizontal pleiotropy.Our findings reveal a causal association between several gut microbiomes and ASD. These results deepen our comprehension of the role of gut microbiota in ASD's pathology, providing the foothold for novel ideas and theoretical frameworks to prevent and treat this patient population in the future.